Unraveling the Link between Financial Literacy and Financial Capability among Java's Students: Mengurai Hubungan antara Literasi Keuangan dan Kemampuan Finansial di Kalangan Pelajar di Jawa - Rismaya Fitria, Rema; Rahayu, Dewi Pudji; Septiana, Mila; Arrasid, Jundi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2023)
This study aims to investigate the relationship between various dimensions of financial literacy, including financial behavior, attitude, knowledge, and capability, among university students in Java. The research encompassed the entire population of university students on Java island in 2022, totaling 3.5 million, with a final sample size of 173 respondents selected using the Slovin formula. Data collection was conducted through a questionnaire survey, and multiple regression analysis was employed to assess the direct influence of financial literacy on financial capability using SPSS software version 25. The findings revealed a significant positive impact of financial behavior and attitude on the financial capability of college students. These results offer valuable insights for policymakers, highlighting the importance of comprehensive strategies in enhancing financial capability, particularly among university students, for improved financial well-being and preparedness.